TRADO-MODERN COMMUNICATION STRATEGIES FOR EFFECTIVE IMPLEMENTATION OF COMMUNITY DEVELOPMENT PROGRAMMES IN BAYELSA STATE, NIGERIA - MORGAN, GILPIN; Hanachor, M.E.; OYEBAMIJI, M.A. (International Journal of Research -GRANTHAALAYAH, 2021)
This study examined trado-modern communication strategies for effective implementation of community development programmes in Bayelsa State, Nigeria. Two objectives and two research questions guided the study. The study adopted descriptive survey and exploratory research designs. 405 respondents were adopted as sample size through total enumeration sampling. A structured questionnaire titled “Trado-Modern Communication Strategies for Effective Implementation of Community Development Programmes” (QT-MCSIECDP) with r = 0.82 was used for data collection. The instrument was validated by experts from the Department of Adult and Non-Formal Education in the University of Port Harcourt, Nigeria. Data were analysed using frequency, percentage and mean statistics. Results show that traditional rulers, groups, town-criers, face-to-face interaction and village squares are the available trado-modern communication channels for effective implementation of community development programmes in Bayelsa State; trado-modern communication keeps the communities up-to-date and enables individuals to react knowledgeably and intelligently to the environment, communicates feelings, creates acceptable changes in behaviour, boosts information, shows ways to solve problems and further growth for effective implementation of community development programmes in Bayelsa State. The study recommended among others that traditional rulers, town-criers, groups, village square and face-to-face interaction should always be used to inform, convince and motivate the community citizens for effective implementation of community development programmes.